Analysis And Design Of Slender Reinforced Concrete Columns - A Realistic Approach - et. al., Vinayagam Ponnusamy, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Reinforced Concrete columns with larger height with respect to lateral dimension are subjected to significant lateral deformation on application of external load (either axial or eccentrical) and subsequently develop secondary moment. This moment induces additional deflection and hence there is an increase in secondary moment. As a result the load-moment curve becomes non-linear. It is obvious that due to this secondary moment the load carrying capacity of the column is reduced. Prediction of ultimate load for reinforced concrete slender columns involves study of buckling through material non-linearity and cracking behaviour of cross section, since the failure occurs in inelastic range. The present design methods of reinforced concrete slender columns suggested by American, British and Indian code provisions are either empirical or involve cumbersome procedure. To circumvent the above, a simple, realistic and rational theory is proposed, incorporating the behaviour of reinforced concrete slender columns rectangular in cross section, bent in single curvature. The theory also incorporates the material non-linearity and effect of cracking at the time of failure. An experimental investigation is undertaken to validate the theory developed. In addition, design charts are prepared based on the theory and a realistic design procedure is proposed for practical applications.